Sexual functioning and its correlates in premenopausal married Indian women with systemic lupus erythematosus. (19th August 2019) - Pinto, Benzeeta; Grover, Sandeep; Dhooria, Aadhaar; Rathi, Manish; Sharma, Aman
Abstract: Background: This study aimed to evaluate sexual functioning and its association with disease activity, damage, marital satisfaction, fatigue and psychiatric comorbidity in married women with systemic lupus erythematosus (SLE). Methods: One hundred and twelve premenopausal married women with SLE were included in the study. Disease activity and damage were assessed using Safety of Estrogens in Lupus Erythematosus National Assessment Systemic Lupus Erythematosus Disease Activity Index (SELENA‐SLEDAI) and Systemic Lupus International Collaborating Clinics/ American College of Rheumatology Damage Index (SDI) respectively. Female sexual function index (FSFI) and couple satisfaction index (CSI) were used to evaluate sexual function and marital satisfaction respectively. Depression, anxiety and fatigue were assessed using Patient Health Questionnaire 9 (PHQ9), Generalized Anxiety Disorder 7 (GAD7) and fatigue severity scale (FSS) respectively. Results: The mean age of the study group was 34.0 (SD 6.8) years. Mean SELENA‐SLEDAI was 3.67 (SD 4.2) and mean SDI was 0.25 (SD 0.62). Median steroid dose at the time of evaluation was 7.5 mg/d of prednisolone. Based on FSFI total score, impaired sexual functioning was found in 60.7%. However, when the cut‐off of different domains was considered, more than 90% of the participants reported problems in desire, arousal and lubrication. The mean CSI score was 130.39 ± 26.17. Eighteen patients (16.1%) had CSI lower than the cut‐off score (104.5) suggestive of marital distress. On univariate analysis sexual function showed a correlation with marital satisfaction ( r  = .34, P  < .001), dose of steroids( r  = −.26, P  = .008), disease activity ( r  = −.21, P  = .027), depression ( r  = −.19, P =  .039) and anxiety ( r  = −.201, P  = .034). Conclusion: Sexual dysfunction is highly prevalent in premenopausal married females with SLE. Higher dose of steroids, disease activity, depression, anxiety and marital satisfaction were associated with poor sexual functioning in one or more domains.